Controllable assembly of multicarboxylic acids functionalized heteropolyoxomolybdates and allochroic properties1. Issue 18 (14th May 2015) - Liang, Yanfen; Li, Suzhi; Yang, Donghui; Ma, Pengtao; Niu, Jingyang; Wang, Jingping
<x xml:space="preserve">Abstract</x> A series of multicarboxylic acids functionalized telluromolybdates have been obtained and their allochroic properties have been researched.